Potential forensic application of receptor for advanced glycation end products (RAGE) and aquaporin 5 (AQP5) as novel biomarkers for diagnosis of drowning. (February 2019) - Lee, So-Yeon; Ha, Eun-Ju; Cho, Hye-Won; Kim, Hye-Rim; Lee, Dongsup; Eom, Yong-Bin
Abstract: Drowning is the most common cause of unnatural death worldwide. There is no single biomarker to diagnose drowning, so the diagnosis of drowning is one of the most difficult tasks in forensic medicine. Especially, distinguishing a victim of drowning from a body disposed of in water following death remains a problem. The objective of this study was to identify specific biomarkers of drowning compared with other causes of death such as hypoxia and postmortem submersion. The present study investigated the intrapulmonary expression of receptor for advanced glycation end products (RAGE), aquaporin-5 (AQP5), surfactant protein-A (SP-A), interleukin 6 (IL-6) and interleukin 1β (IL-1β) as markers of drowning. In animal experiments, all rats (n = 45) were classified into four groups (drowning, postmortem-submersion, hypoxia and control group). The lungs of experimental animals were analyzed as mRNA expression, immunoblot expression and immunohistochemical staining. qRT-PCR demonstrated increased mRNA expression of RAGE and AQP5 in drowning group compared with that in control, hypoxia and postmortem-submersion group, but not other molecules. Western blotting also showed high expression of RAGE and AQP5 in drowning group, immunostaining of RAGE and AQP5 was highly detected in a linear pattern in type I alveolar epithelial cells, compared with control and postmortem-submersion group. These observations indicate a difference of expression in pulmonary molecular pathology compared with other causes, suggesting RAGE and AQP5 may be useful for differentiation between drowning and postmortem-submersion. Highlights: RAGE and AQP5 mRNA showed increased expression in drowning compared with postmortem-submersion. Western blotting and IHC staining analysis also showed high expression of RAGE and AQP5 in drowning group. RAGE and AQP5 can be helpful to differentiate drowning from postmortem-submersion.